Manufacturing knowledge management based on STEP-NC standard: a Closed-Loop Manufacturing approach. Issue 9 (2nd September 2017) - Danjou, Christophe; Le Duigou, Julien; Eynard, Benoît
Abstract : The paper presents a proposal to ensure Closed-Loop Manufacturing from CNC machines to CAM systems. The main goal is to manage knowledge from the CNC machine and to reuse it in the CAM system. This proposal aims to help CAM programmers for programming new machining sequences by choosing the best CNC machines parameters. The main contribution of this paper focuses on how to provide guidelines extracted from past CNC programs to the CAM programme for future cases. Although STEP-NC standard enhances bidirectional exchanges in the digital chain, from CAD systems to CNC machines, it does not allow the management of manufacturing knowledge. To achieve the information feedback from CNC machine to CAM system, Closed-Loop Manufacturing approach sets up a manufacturing loop using PLM systems supported by OntoSTEP-NC – an ontology based on STEP-NC. Centred on the Manufacturing Process Management platform Closed-Loop Manufacturing is a three-step process: (1) capitalisation of cutting parameters, the manufacturing features and the material to fill the Manufacturing Process Management database, (2) validation of last machining sequences and (3) manufacturing feature recognition to have the most relevant information integration from the Manufacturing Process Management in the CAM programming stage.